DIAGNOSTIK KESULITAN BELAJAR MATEMATIKA: Studi pada Siswa SD/MI di Kota Makassar - Nursalam Nursalam (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2016)
This research aims to describe students' difficulties in learning mathematics class V SD/MI at Makassar by developing diagnostic tests of mathematics. The study was conducted by performing several steps: determining material that is less dominated by students, devising test diagnostic, identification the alleged difficulties experienced by students. The results showed that mathematics material in class V SD / MI most students experiencing difficulties are the powers and fractional operations. It is caused by a weak ability of arithmetic operations. The inability of students to convert units of time and the distance was other difficulties faced by students. This study provides a product profile that describes the ability of students in solving problem. This student profile information is expected teachers can improve the quality of teaching and the learning process in the classroom so that students do not experience difficulties in learning mathematics.